Determining The Location of Regional Landfill in Kediri District Using Spatial Approach with Geographic Information System Applications - Agnes Tyagita Ayudyaningtyas; Harsuko Riniwati; Agung Murti Nugroho (Asian Journal of Social and Humanities, 2023)
Existing landfills in Kediri Regency and City are experiencing overcapacity conditions which are influenced by the increasing volume of waste along with the increasing population and the rapid development of urban areas. The Regional Landfill in Kediri Regency which is a national project based on Presidential Regulation of the Republic of Indonesia Number 80 of 2019 concerning the Acceleration of Economic Development in the Gresik - Bangkalan - Mojokerto - Surabaya - Sidoarjo - Lamongan, Bromo - Tengger - Semeru, and Selingkar Wilis - Lintas Selatan areas and is part of the Kediri Regency Regional Spatial Plan needs to be analyzed for location feasibility. The feasibility of the location of the Regional Landfill is the goal of this research with a spatial approach using Geographic Information Systems by considering the parameters in SNI 03-3241-1994 concerning Procedures for Selecting the Location of Waste Landfills. The selected variables are constraining factors consisting of regional criteria, namely geological conditions, hydrogeological conditions, slope, protected areas, distance to airfields, flood susceptibility and distance to water bodies. The feasible locations for regional landfill based on spatial analysis using GIS are in Ngadiluwih, Kras, Purwoasri, and Mojo sub-districts.